2017
DOI: 10.1039/c7gc00269f
|View full text |Cite
|
Sign up to set email alerts
|

Direct one-pot conversion of monosaccharides into high-yield 2,5-dimethylfuran over a multifunctional Pd/Zr-based metal–organic framework@sulfonated graphene oxide catalyst

Abstract: A one-pot conversion of monosaccharides (fructose and glucose) into high-yield 2,5-dimethylfuran (2,5-DMF) is demonstrated over a multifunctional catalyst obtained by loading Pd on UiO-66@ sulfonated GO (Pd/UiO-66@SGO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 44 publications
2
96
0
Order By: Relevance
“…Compared with the production of DFF from HMF,t he direct one-pot conversion of monosaccharides (fructosea nd glucose) into DFF with high yield is desirable and still ag reat challenge, [22,41,42] which involves the selectivedehydration of carbohydratesi nto HMF over acid sites and the consequent oxidation of HMF to DFF over redox sites. [22] However,p roduction of DFF has often been obtained in one pot and two steps, including the acidification and oxidation reaction, whichf aces a major drawback in the formation of humins and other undesired byproducts owing to the coexistence of acid and redox sites.…”
Section: Catalytic Activity Of Hpmov/cs-fint He Oxidation Of Monosaccmentioning
confidence: 99%
“…Compared with the production of DFF from HMF,t he direct one-pot conversion of monosaccharides (fructosea nd glucose) into DFF with high yield is desirable and still ag reat challenge, [22,41,42] which involves the selectivedehydration of carbohydratesi nto HMF over acid sites and the consequent oxidation of HMF to DFF over redox sites. [22] However,p roduction of DFF has often been obtained in one pot and two steps, including the acidification and oxidation reaction, whichf aces a major drawback in the formation of humins and other undesired byproducts owing to the coexistence of acid and redox sites.…”
Section: Catalytic Activity Of Hpmov/cs-fint He Oxidation Of Monosaccmentioning
confidence: 99%
“…[94] The HRTEM image of Pd@UiO-66/SGO (4.8 % Pd loading) showed a uniform distribution of Pd NPs with a mean size of 3.5 � 0.5 nm on the particles of UiO-66. In one of these less-abundant examples, Pd was loaded on UiO-66 by impregnation and the particles deposited on sulfonated graphene oxide (Pd@UiO-66/SGO) (SGO stands for sulfonated graphene oxide).…”
Section: Pd Npsmentioning
confidence: 95%
“…[50] In addition, the hydrophilic surface and Brønsted acid of GO can enhance the fructose adsorption onto the surface of the catalysts. [51] In recent years, many research teams reported that the GO has been utilized as a heterogeneous catalyst for various acid-catalyzed reactions, such as hydrolysis of cellulose glucose and fructose. [52][53][54] Therefore, the graft of MOFs on GO support may intend to solve the agglomeration problem and achieve high-efficiency catalytic conversion of glucose to 5-HMF.…”
Section: Introductionmentioning
confidence: 99%